Comparative Transcriptome and iTRAQ Proteome Analyses Reveal the Mechanisms of Diapause in Aphidius gifuensis Ashmead (Hymenoptera: Aphidiidae) - Zhang, Hong-Zhi; Li, Yu-Yan; An, Tao; Huang, Feng-Xia; Wang, Meng-Qing; Liu, Chen-Xi; Mao, Jian-Jun; Zhang, Li-Sheng (Frontiers in Physiology, 2018)
Aphidius gifuensis Ashmead (Hymenoptera: Aphidiidae) is a solitary endoparasitoid used in the biological control of various aphids. Diapause plays an important role in the successful production and deployment of A. gifuensis. Diapause can effectively extend the shelf life of biological control agents and solve several practical production problems like long production cycles, short retention periods, and discontinuities between supply and demand. In recent years, studies have been conducted on the environmental regulation and physiological and biochemical mechanisms of diapause in A. gifuensis. Nevertheless, the molecular mechanism of diapause in this species remains unclear. In this study, we compared the transcriptomes and proteomes of diapause and non-diapause A. gifuensis to identify the genes and proteins associated with this process. A total of 557 transcripts and 568 proteins were differentially expressed between the two groups. Among them, (1) genes involved in trehalose synthesis such as glycogen synthase, glycogen phosphorylase, and trehalose 6-phosphate synthase were upregulated in diapause at mRNA or protein level while glycolysis and gluconeogenesis-related genes were downregulated, suggesting that A. gifuensis stores trehalose as an energy resource and cryoprotectant; (2) the expression of immune-related genes like C-type lectins, hemocyanin, and phenoloxidase was increased, which helps to maintain immunity during diapause; (3) a chitin synthase and several cuticular protein genes were upregulated to harden the cuticle of diapausing A. gifuensis larval. These findings improve our understanding of A. gifuensis. diapause and provide the foundation for further pertinent studies.